LILRB4 on multiple myeloma cells promotes bone lesion by p-SHP2/NF-κB/RELT signal pathway - Hongying Wang; Lei Wang; Huiwen Luan; Jing Xiao; Zhiling Zhao; Pengfei Yu; Mi Deng; Yifan Liu; Shuhao Ji; Junjie Ma; Yan Zhou; Jiashen Zhang; et al. (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background Leukocyte Ig-like receptor B family 4 (LILRB4) as an immune checkpoint on myeloid cells is a potential target for tumor therapy. Extensive osteolytic bone lesion is the most characteristic feature of multiple myeloma. It is unclear whether ectopic LILRB4 on multiple myeloma regulates bone lesion. Methods The conditioned medium (CM) from LILRB4-WT and -KO cells was used to analyze the effects of LILRB4 on osteoclasts and osteoblasts. Xenograft, syngeneic and patient derived xenograft models were constructed, and micro-CT, H&E staining were used to observe the bone lesion. RNA-seq, cytokine array, qPCR, the activity of luciferase, Co-IP and western blotting were used to clarify the mechanism by which LILRB4 mediated bone damage in multiple myeloma. Results We comprehensively analyzed the expression of LILRB4 in various tumor tissue arrays, and found that LILRB4 was highly expressed in multiple myeloma samples. The patient’s imaging data showed that the higher the expression level of LILRB4, the more serious the bone lesion in patients with multiple myeloma. The conditioned medium from LILRB4-WT not -KO cells could significantly promote the differentiation and maturation of osteoclasts. Xenograft, syngeneic and patient derived xenograft models furtherly confirmed that LILRB4 could mediate bone lesion of multiple myeloma. Next, cytokine array was performed to identify the differentially expressed cytokines, and RELT was identified and regulated by LILRB4. The overexpression or exogenous RELT could regenerate the bone damage in LILRB4-KO cells in vitro and in vivo. The deletion of LILRB4, anti-LILRB4 alone or in combination with bortezomib could significantly delay the progression of bone lesion of multiple myeloma. Conclusions Our findings indicated that LILRB4 promoted the bone lesion by promoting the differentiation and mature of osteoclasts through secreting RELT, and blocking LILRB4 singling pathway could inhibit the bone lesion.